The Balto-Slavic word for ‘crane’ and its cognates - Kortlandt, Frederik (Baltistica, 2018)
Balto-Slavic *gerHōu, obl. *gerHu‑ from Indo-European *ǵerH2ōu, *grH2u‑ beside *ǵerH2‑H1ēn, *grH2‑H1n‑ reflected in other languages.
Keywords: Balto-Slavic; Indo-European; etymology; crane